Identifying herbicide-tolerant traits and developing herbicide strategies for weed control in pearl millet [Pennisetum glaucum (L.) R. Br.] - Tugoo, Midhat Zulafkar (My University, 2025)
Weed management in pearl millet [Pennisetum glaucum (L.) R. Br.] presents a significant production challenge. The limited options for herbicides further complicate this issue. Additionally, the widespread evolution of herbicide resistance among weed species exacerbates the difficulty of management strategies. The main objectives of this thesis were to 1) identify and characterize the sensitivity of 56 pearl millet parental lines to POST-applied clethodim (136 g ai ha⁻¹), quizalofop-p-ethyl (QPE) (77 ai g ha⁻¹), imazamox (52 g ai ha⁻¹) and nicosulfuron (70 g ai ha⁻¹), and 2) investigate eight preemergence (PRE) herbicides (labeled in sorghum) for crop safety and weed control in three pearl millet hybrids, and 3) test various postemergence (POST) herbicides for crop safety and weed control in pearl millet hybrids. All tested parental lines were found sensitive to clethodim and QPE, with only four lines showing minimal survival (2% to 12%) but still suffering significant injury (90% to 95%) at 21 days after application (DAA). However, variable responses were observed to both imazamox and nicosulfuron. The survival rate with imazamox and nicosulfuron ranged from 70% to 100%, with visible injury and biomass reduction ranging from 5% and 70%. Three pearl millet parental lines with low sensitivity to imazamox (ARCH35R, 45R, and 73R), two lines with low sensitivity to nicosulfuron (ARCH45R and 73R), one line with high sensitivity (ARCH21B), and a susceptible sorghum (Sorghum bicolor L. Moench) hybrid (P84G62) to both herbicides were further characterized. Dose-response assays revealed that ARCH35R, 45R, and 49R were significantly less sensitive to imazamox, with reduced sensitivity of 7.7- to 12.2-fold compared to the highly sensitive ARCH21B and the sorghum hybrid. For nicosulfuron, ARCH45R and 49R showed 2.5- to 6.0-fold reduced sensitivity compared to ARCH21B and the sorghum hybrid. These findings represent the first report of reduced sensitivity to imazamox and nicosulfuron in pearl millet lines, suggesting these lines could be useful for managing grass weeds in the field. The second objective focused on evaluating eight preemergence (PRE) herbicides, including S-metolachlor, acetochlor, atrazine, and mesotrione, and their combinations for crop safety and weed control in three pearl millet hybrids in a field study over two growing seasons. Results showed that the application of S-metolachlor alone or in combination with atrazine, mesotrione, or both caused severe injury (>95%) to all three hybrids at 28 DAA. In contrast, mixtures of acetochlor with atrazine showed variable injury levels, ranging from 50% to 96% across three hybrids. However, atrazine or mesotrione applied alone or in combination caused minimal injury (<5%) to the hybrids, indicating good crop safety. Regarding weed control, all tested PRE herbicides provided excellent control of Palmer amaranth, with control levels reaching ≥90% at 28 DAA, except for S-metolachlor (86% control). The combination of mesotrione and acetochlor with atrazine was especially effective against green foxtail, achieving ≥ 99% control. These results suggest that the combination of atrazine, mesotrione, and their mixtures can be used safely for controlling Palmer amaranth and green foxtail in pearl millet without causing significant crop injury. The third objective evaluated the safety and effectiveness of postemergence (POST) herbicides on five pearl millet hybrids in greenhouse and three hybrids in field study. In the greenhouse study, all POST herbicides caused only minimal injury (1% to 5%) at 28 DAA, except for imazamox and nicosulfuron, which caused moderate injury (22% to 27%). Similarly, field studies showed minimal injury (1% to 3%) from all the POST herbicides, except imazamox and nicosulfuron. POST herbicides, including 2,4-D, dicamba, bromoxynil + pyrasulfotole, and the combination of 2,4-D + bromoxynil + fluroxypyr provided 88% to 91% control of Palmer amaranth and significantly reduced its density (2 to 4 plants m⁻²). In contrast, imazamox and nicosulfuron were less effective in controlling Palmer amaranth, with only 60% to 65% control and a higher density of 8 plants m⁻². However, imazamox and nicosulfuron were effective against green foxtail, providing 91% to 92% control and reducing its density to 2 plants m⁻² at 42 DAA. Among all tested hybrids, the Hyb1 outperformed the other hybrids at two field sites. The combination of 2,4-D + bromoxynil + fluroxypyr resulted in the highest grain yield for Hyb1 (3,866 to 4,619 kg ha⁻¹), Hyb2 (2,222 to 3,699 kg ha⁻¹), and Hyb3 (822 to 1,315 kg ha⁻¹). Overall, results from this thesis provide valuable insights into the herbicide sensitivity of pearl millet and its potential use for weed control. Reduced sensitivity to imazamox and nicosulfuron in pearl millet lines may potentially be used in developing herbicide-tolerant cultivars. Additionally, PRE herbicide applications, particularly those involving atrazine and mesotrione, showed promise for controlling Palmer amaranth and green foxtail while maintaining crop safety. Majority of tested POST herbicides were found to be safe for pearl millet and effective in controlling Palmer amaranth. POST applied imazamox and nicosulfuron were found particularly effective against green foxtail. Overall, these results highlight the potential for using selective PRE and POST herbicide strategies tested in this research to improve weed management in pearl millet production.
Keywords: Pearl millet; Preemergence; Postemergence; Herbicide tolerance; Central Great Plains; Weed control